WHEELED MOBILE ROBOT WITH GPS-BASED WAYPOINT NAVIGATION SYSTEM AND IOT APPLICATION - Maharani, Suci; Panjaitan, Seno Darmawan; Marindani, Elang Derdian (Faculty of Engineering, Universitas Tanjungpura, 2025)
Technological advances in robotics have had a significant impact on various aspects of human life. One of them is a mobile robot that is able to move from one place to another using wheels. This study designs a mecanum wheeled robot that can move with a waypoint navigation system using a GPS coordinate system and IoT applications. Based on the test results, it is known that the Ublox Neo-6M GPS sensor can determine the location coordinates quite well in an open area without obstacles with an active time of 2-5 minutes. The HMC5883L compass sensor has an angle reading with the smallest error of 2 ° in the north direction. The results of this study, the robot can go to the targeted position without obstacles with varying angle and distance direction accuracy based on the readings of the compass sensor and infrared sensor as a distance measuring encoder at each waypoint. Testing the waypoint robot in conditions without obstacles, obtained a better level of angle and distance accuracy of the robot at waypoint 3 of 98.87% and 95.69%. When there are obstacles, the angle accuracy of waypoint 3 becomes 97.43%, and the distance accuracy is better at waypoint 1 to 94.2%. IoT application with Kodular can be used to operate robots via Bluetooth serial communication which takes an average time of about 0.507 seconds at a distance of 10 meters. At a distance of more than 11 meters, Bluetooth communication cannot connect to the HC-05 Bluetooth module.